If it's not what You are looking for type in the equation solver your own equation and let us solve it.
63=3x+3(2x-15)
We move all terms to the left:
63-(3x+3(2x-15))=0
We calculate terms in parentheses: -(3x+3(2x-15)), so:We get rid of parentheses
3x+3(2x-15)
We multiply parentheses
3x+6x-45
We add all the numbers together, and all the variables
9x-45
Back to the equation:
-(9x-45)
-9x+45+63=0
We add all the numbers together, and all the variables
-9x+108=0
We move all terms containing x to the left, all other terms to the right
-9x=-108
x=-108/-9
x=+12
| B^2=-9b | | -n+8+5n=16 | | 3c-30=27 | | -7k+19k+-16=8 | | 2/x=6/100 | | 3x+27=4x+16 | | -2(4+5r)-4r=-120 | | 3(5x)+2=7x+11 | | (3/4)d=36 | | 0.2(4x-0.1)=0.06 | | -1+3/2y=8 | | 3x–6=x–2 | | -12=3-2p-3p | | -1+32y=8 | | 2x+12+2x+5+7x-1=180 | | 3v-30=v-15 | | -6k-6=102 | | 8=0.5e3 | | 3x-4=9x+44. | | ((1/2+x)+4)+((3/4+x)-6)=2x-47 | | 9x/3=33,x= | | x/7-12=13 | | 2.1c=27.3 | | 3x-6/x+1=0 | | 3x+2(5x-15)=50 | | 7m+6=-55 | | 3/5x19=16 | | 0.26(x-14)=7 | | p3− –7=11 | | 8x+38=-(-6-4x) | | F(x)=3x²-9x–54 | | 6/x+8=15 |